Hubungan Self-Efficacy dengan Subjective Well-Being pada Lanjut Usia - Merry Pongdatu; Frischa Alvionita (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2026)
The older adult are a vulnerable group to a decline in quality of life due to physical, psychological, and social changes. One factor that can affect the quality of life of the elderly is Self-Efficacy, or the belief in one's ability to face life's challenges. This study aimed to determine the relationship between Self-Efficacy and Subjective Well-Being among the older adult in the working area of Lepo-Lepo Public Health Center, Kendari City. This was a quantitative study with a cross-sectional design. The population consisted of 2,801 older adult individuals, with a sample of 97 respondents selected using cluster random sampling. Data were collected using the General Self-Efficacy Scale (GSES) and the Subjective Well-Being Scale. Data analysis used the chi-square test. The results showed that most elderly had good Self-Efficacy (67%) and good Subjective Well-Being (84.5%). Statistical tests showed a significant relationship between Self-Efficacy and Subjective Well-Being with a chi-square value of x² = 29.228 > x² table = 3.841 and φ = 0.549, indicating a moderate relationship. It is expected that this research can be a basis for healthcare providers, especially nurses, in developing intervention programs to improve the quality of life of the elderly through increased Self-Efficacy.